Peran Koperasi Sekolah dalam Meningkatkan Semangat Kewirausahaan terhadap Peserta Didik Tingkat SMA/MA di MAN 2 Model Medan - Rezeki Daifatun Hasanah; Ripho Delzy Perkasa (STKIP PGRI SITUBONDO, 2023)
The aspect of developing the personality of students is the school environment. Personality development is not only in the learning stages, but can provide students with knowledge and expertise in society and social life. The school cooperative is an aid that can build students, which is distributed by the school for the student section. In arousing the entrepreneurial spirit of students, that school must form a cooperative in a school institution. This type of research is to direct and inform the function of school cooperatives in increasing the entrepreneurial spirit of SMA/MA level students at MAN 2 Model Medan. Where this research is a descriptive qualitative research, using a fact-based unification tool in the form of interviews and observations, and taking from various sources such as reference books, journals, and the internet. In the analysis carried out in fact, the researcher uses reduction facts, display facts, and couclusion drawing (fact verification). Based on the results of this study, the function of school cooperatives in increasing the spirit of entrepreneurship in students is growing and developing so that students are enthusiastic about entrepreneurship.